Facile one-pot reduction of β-nitrostyrenes to phenethylamines using sodium borohydride and copper(II) chloride - D’Andrea, Laura; Jademyr, Simon (Beilstein Journal of Organic Chemistry, 2025)
Phenethylamines and phenylisopropylamines of scientific relevance can be prepared with a NaBH4/CuCl2 system in 10 to 30 minutes via reduction of substituted β-nitrostyrenes. This one-pot procedure allows the quick isolation of substituted β-nitrostyrene scaffolds with 62–83% yield under mild conditions, without the need for special precautions, inert atmosphere, and time-consuming purification techniques.
Keywords: 2C-X; CuCl2; NaBH4; β-nitrostyrene; phenethylamine